Interventional Palliation of Painful Extraspinal Musculoskeletal Metastases - Tomasian, Anderanik; Jennings, Jack W. (Seminars in Interventional Radiology, 2022)
The musculoskeletal system is commonly involved by metastases, and skeletal-related events such as intractable pain due to direct osseous tumor involvement, pathologic fracture, and neurologic deficits as a result of nerve compression often adversely affect patient's quality of life. There have been substantial advances in percutaneous minimally invasive musculoskeletal oncologic interventions for the management of patients with musculoskeletal metastases including thermal ablations, cementation with or without osseous reinforcement via implants, osteosynthesis, neurolysis, and palliative injections which are progressively incorporated in clinical practice. These interventions are performed, in conjunction with or supplemented by adjuvant radiation therapy, systemic therapy, surgery, or analgesics, to achieve durable pain palliation, local tumor control, or cure. This article reviews minimally invasive percutaneous image-guided musculoskeletal oncologic interventions for the management of patients with extraspinal musculoskeletal metastases.
Keywords: musculoskeletal oncology; thermal ablation; cementoplasty; osteosynthesis; thermal protection; neurolysis; interventional radiology